Dissociation in Optokinetic Stimulation Sensitivity between Omission and Substitution Reading Errors in Neglect Dyslexia - Daini, Roberta; Albonico, Andrea; Malaspina, Manuela; Martelli, Marialuisa; Primativo, Silvia; Arduino, Lisa S. (Frontiers in Human Neuroscience, 2013)
Although omission and substitution errors in neglect dyslexia (ND) patients have always been considered as different manifestations of the same acquired reading disorder, recently, we proposed a new dual mechanism model. While omissions are related to the exploratory disorder which characterizes unilateral spatial neglect, substitutions are due to a perceptual integration mechanism. A consequence of this hypothesis is that specific training for omission-type ND patients would aim at restoring the oculo-motor scanning and should not improve reading in substitution-type ND. With this aim we administered an optokinetic stimulation to two brain-damaged patients with both unilateral spatial neglect and neglect dyslexia, MA and EP, who showed ND deficits mainly characterized by omissions and substitutions, respectively. MA also showed an impairment in oculo-motor behaviour with a non-reading task, while EP did not. The two patients presented a dissociation with respect to their sensitivity to optokinetic stimulation so that, as expected, MA was positively affected, while EP was not. Our results confirm a dissociation between the two mechanisms underlying omission and substitution reading errors in ND patients. Moreover, they suggest that such a dissociation could possibly be extendeds to the effectiveness of rehabilitative procedures, and that patients who mainly omit contralesional-sided letters would benefit from optokinetic stimulation.